Penguasaan Konsep pada Hukum Archimedes Siswa SMA - Lestari Widodo; Lia Yuliati; Parno Parno (Graduate School of Universitas Negeri Malang, 2018)
Abstract: The purpose of this study was to describe students’ concept mastery on Archimedes’ principle. The method of this study was descriptive method. The instrument of concept mastery test of this study was consisted of 4 essay questions with reliability Cronbach’s alpha 0.67. This study was the study case in one of class in SMAN 8 Muaro Jambi. The subjects of this study were 27 students. The result shows that the average of students’ concept mastery is 33,00 with scale 0 to 100. It was low category. The students found difficulties to be applied the concept of Archimedes principle toward a problem. Moreover, the students found difficulties to be intrepreted a problem with figure so the students found difficult to be related to Archimedes principle.Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan penguasaan konsep siswa pada submateri Hukum Archimedes. Metode penelitian yang digunakan adalah metode deskriptif. Instrumen tes penguasaan konsep penelitian ini terdiri atas empat soal esai dengan reliabilitas Cronbach’s alpha 0.67. Penelitian ini merupakan study kasus di salah satu kelas di SMAN 8 Muaro Jambi. Subjek penelitian terdiri atas 27 siswa. Hasil menunjukkan bahwa penguasaan konsep siswa pada submateri hukum Archimedes memiliki rata-rata 33,00 dengan skala 0—100, hasil tersebut tergolong rendah. Siswa mengalami kesulitan dalam menerapkan konsep hukum Archimedes terhadap permasalahan yang diberikan. Siswa mengalami kesulitan dalam menginterpretasikan permasalahan berupa gambar sehingga siswa mengalami kesulitan untuk mengaitkan dengan hukum Archimedes.